NEGATIVE INTEREST RATES: CENTRAL BANKS INITIATED AN EXPERIMENT - A. N. Burenin (Vestnik MGIMO-Universiteta)
Negative interest rates appeared as a consequence of economic problems that countries with market economy came across after the crises of2007-2008. The attempts of monetary authorities to stimulate economies with the help of quantitative easing didn't bring the desired result. That's why the central banks once again resorted to a traditional tool of their monetary policy of changing interest rates. But this time they launched an experiment, they used negative interest rates. The European Central Bank, the Swedish Riksbank, the Bank of Japan, and the National Bank of Hungary introduced negative rates in order to stimulate economic growth and fight the threat of deflation, the Danish National Bank and the Swiss National Bank tried to deter appreciation of their currencies. Negative rates of the central banks brought about negative yields of government and nongovernment securities in several countries. The problem acquires an aggravated form due to the fact that negative rates appeared in several European countries simultaneously at the moment when global financial markets were not in crises. Some questions arise concerning the negative rates, for example, how low can central banks bring down the rates in the future, what is their influence on the stock markets, what is the reaction of depositors to the introduction of negative deposit rates by commercial banks, must one consider a negative rate as a rate of interest or payment to store money of the depositor, in which circumstances negative rates can be justified to fight deflation. The last question plays an important role, because recent studies find that positive economic growth is possible during deflation. If central banks don't take this nuance into consideration, they can create economic imbalances by increasing liquidity. Negative rates are not as inoffensive as it may seem at first glance. Not far ago an investor, who tried to averse risk, was buying government securities. Their yields according to theory could not become lower than zero. By introducing negative rates, the central banks told in fact that the lower bound of the interest rate didn't exist any more. Thus, now investors find themselves in a situation of complete uncertainty, and risk becomes an absolute dominance. They can't averse it even in government securities. Such situation influences financial markets in a negative way. If we go up to a higher level of abstraction and imagine an economy as a live organism, which tries to rehabilitate itself, then the negative rates can be considered as a way through which the economy tries to solve the task of reducing liquidity. Studies show that so far the introduction of modestly negative rates have not affected the functioning of money markets much. In anticipation of the forthcoming cyclical crisis it is possible to give advice to the central banks to make one more step in the issue of the development of new tools of monetary regulation. Such new tools could be represented by futures contracts on interest rates securities.